The effect of smartwatches on patient-centered healthcare - Ndhlovu, Patson (University of the Witwatersrand, Johannesburg, 2022)
Patient-centered healthcare lies at the core of health and social services, where individuals are recognized and encouraged to take an active role in their own care. The literature suggests that technological advancements are contributing to achieving patient-centred care. As technology is advancing, it is important to keep abreast of how emerging technologies are affecting patient-centred healthcare. Thus, the purpose of this study was to investigate the effects of smartwatches on patient-centred healthcare. To achieve this, this study assessed the effect of features of smartwatches on the Picker's 8 principles of patient-centred healthcare. The sample for this study was 141 participants who use smartwatches. These participants were all part of a running club based in Gauteng province of South Africa. The findings revealed that the activity tracking feature of a smartwatch has a moderate impact on emotional comfort and coordination and integration of care. Similarly, the vital signs monitoring feature has a moderate effect on the continuity and transition of care, while the data management feature demonstrated a moderate effect on the coordination and integration of care. Moreover, the activity tracking feature of a smartwatch has the strongest effect on the coordination and integration of care, while vital signs monitoring has the strongest effect on the continuity and transition of care. The data management feature, on the other hand, has the strongest effect on the coordination and integration of care. Findings from this study, albeit their limitations, can assist healthcare providers to make informed decisions on which features of smartwatches they should focus on when promoting the use of wearables to provide patient-centred car
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, School of Accountancy, University of the Witwatersrand, Johannesburg, 2022
Keywords: Smartwatches; Wearables; Healthcare; Patient-centered healthcare; vital signs monitoring; Data management; Physical activity; UCTD; SDG-3: Good health and well-being